Green banana biomass: functional food, a review (Research, Society and Development, 2022)
The increasing demand for functional and/or healthy foods has been significant in recent years. The banana, while green and cooked consists mostly of resistant starch, which is a functional food of the prebiotic type. The present work brings a literature integrative review of the period of the last 5 years in the following databases: LILACS (Latin American and Caribbean Literature in Health Sciences), MedLine (Medical Literature Analysis and Retrieval System Online), SciElo (Scientific Electronic Library Online). With the following keywords: biomass, green banana biomass, green banana, functional food. A filter was applied to articles relevant to the topic. Subsequently, duplicate, repeated articles, published in more than one database were discarded. After a systematic analysis, the relevant information was listed in the present work.